Benzalacetone Synthase - Abe, Ikuro (Frontiers in Plant Science, 2012)
Benzalacetone synthase, from the medicinal plant Rheum palmatum (Polygonaceae) (RpBAS), is a plant-specific chalcone synthase (CHS) superfamily of type III polyketide synthase (PKS). RpBAS catalyzes the one-step, decarboxylative condensation of 4-coumaroyl-CoA with malonyl-CoA to produce the C6-C4 benzalacetone scaffold. The X-ray crystal structures of RpBAS confirmed that the diketide-forming activity is attributable to the characteristic substitution of the conserved active-site "gatekeeper" Phe with Leu. Furthermore, the crystal structures suggested that RpBAS employs novel catalytic machinery for the thioester bond cleavage of the enzyme-bound diketide intermediate and the final decarboxylation reaction to produce benzalacetone. Finally, by exploiting the remarkable substrate tolerance and catalytic versatility of RpBAS, precursor-directed biosynthesis efficiently generated chemically and structurally divergent, unnatural novel polyketide scaffolds. These findings provided a structural basis for the functional diversity of the type III PKS enzymes.